Anxiety, stress, and depression in Australian pregnant women during the COVID-19 pandemic: A cross sectional study. (April 2023) - Davis, D; Sheehy, A; Nightingale, H; de Vitry-Smith, S; Taylor, J; Cummins, A
Abstract: Background: The COVID-19 pandemic necessitated rapid responses by health services to suppress transmission of the virus. Aim: This study aimed to investigate predictors of anxiety, stress and depression in Australian pregnant women during the COVID-19 pandemic including continuity of carer and the role of social support. Methods: Women aged 18 years and over in their third trimester of pregnancy were invited to complete an online survey between July 2020 and January 2021. The survey included validated tools for anxiety, stress, and depression. Regression modelling was used to identify associations between a range of factors including continuity of carer, and mental health measures. Findings: 1668 women completed the survey. One quarter screened positive for depression, 19% for moderate or higher range anxiety, and 15.5% for stress. The most significant contribution to higher anxiety, stress, and depression scores was a pre-existing mental health condition, followed by financial strain and a current complex pregnancy. Protective factors included age, social support, and parity. Discussion: Maternity care strategies to reduce COVID-19 transmission restricted women's access to their customary pregnancy supports and increased their psychological morbidity. Conclusion: Factors associated with anxiety, stress and depression scores during the COVID-19 pandemic were identified. Maternity care during the pandemic compromised pregnant women's support systems.